Complex Cobalt Sulfide Nanobubble Cages with Enhanced Electrochemical Properties. Issue 7 (12th June 2017) - Guan, Bu Yuan; (David) Lou, Xiong Wen
Abstract : Metal–organic frameworks (MOFs) have been widely employed as precursors to prepare various nanostructured functional materials. Here, a "nanoparticles‐in‐MOF" dual‐template approach for generating complex cobalt sulfide (CoS) nanobubble cages is reported. A novel nanoparticles‐in‐MOF hybrid structure consisting of a Co‐based MOF polyhedron host and many encapsulated mesostructured TiO2 nanospheres is first prepared, followed by a sulfidation process to obtain a complex cage structure consisting of CoS nanobubbles in the shell. Importantly, this strategy can be extended to prepare many other functional nanoparticles‐in‐MOF hybrid structures. When evaluated as an electrode material for hybrid supercapacitors, the as‐derived CoS nanobubble cages display remarkable electrochemical performance with long cycle life and good rate capability. Abstract : A "nanoparticles‐in‐metal–organic framework" dual‐template method is developed to synthesize CoS nanobubble cages. With their structural advantages, these unique CoS nanobubble cages exhibit enhanced electrochemical performance as an electrode material for hybrid supercapacitors.